Implementasi Contextual Learning dalam Pembelajaran Pendidikan Agama Islam - Naimi, Nadlrah; Sakinah, Nur (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
Islamic religious education is a process of transformation and realization of the values of Islamic teachings through learning, both formal and non-formal to the community (students) to be lived, understood and practiced in everyday life. The method used in this study uses a qualitative approach. The results of this study indicate that to realize and realize the values of Islamic teachings, strategies or learning models are needed that can be applied by students. One strategy that can be applied is learning in the form of Contextual Learning which is a learning strategy that seeks to connect the material being studied with the context of real life, not only transferring knowledge from teacher to student, but students can do, try and reconstruct the teaching material themselves. from the teacher and correlated in real life and the hope is that students can solve the problems faced both for themselves, their families and the community.